Information System Strategic Planning Based On Togaf Adm Framework In 2nd Revenue Functions Dinas Pendapatan Dan Pengelolaan Keuangan Bandung Regency - Anisa Fatakh Sabila; Yuli Adam Prasetyo; Ridha Hanafi (eProceedings of Engineering, 2016)
Dinas Pendapatan dan Pengelolaan Keuangan (DPPK) Bandung Regency is a regional organization as a support element local government headed by a Chief and is responsible to Regent through the Secretary of Bandung Regency. Nowadays, DPPK Bandung Regency have focus services in tax services. Tax services manageable by 1st Revenue Division and 2nd Revenue division. For 2nd Revenue Division manage PBB and BPHTB. In services process 2nd Revenue functions has E-Tax system for facilitate the PBB and BPHTB services. Before developing E-Tax, 2nd Revenue division should make information system strategic planning that guarantee implement to be optimal and can fulfil the business needs. Information system strategic planning (ISSP) has been recognized for its contribution to organizations and has become a very challenging subject for scientists and practitioners in the recent years. Framework that support for developing ISSP in this research is TOGAF ADM, focusing in Phase F which is opportunities and solutions. Keywords: information system strategic planning, TOGAF ADM, 2nd Revenue division